Peptide Nucleic Acid-Mediated PCR Clamping as a Useful Supplement in the Determination of Microbial Diversity - von Wintzingerode, Friedrich (American Society for Microbiology, 2000)
Peptide nucleic acid (PNA)-mediated PCR clamping (H. Ørum, P. E. Nielsen, M. Egholm, R. H. Berg, O. Buchardt, and C. Stanley, Nucleic Acids Res. 21:5332–5336, 1993) was introduced as a novel procedure to selectively amplify ribosomal DNAs (rDNAs) which are not frequently found in clone libraries generated by standard PCR from complex microbial consortia. Three different PNA molecules were used; two of these molecules (PNA-ALF and PNA-EUB353) overlapped with one of the amplification primers, whereas PNA-1114F hybridized to the middle of the amplified region. Thus, PCR clamping was achieved either by competitive binding between the PNA molecules and the forward or reverse primers (competitive clamping) or by hindering polymerase readthrough (elongation arrest). Gene libraries generated from mixed rDNA templates by using PCR clamping are enriched for clones that do not contain sequences homologous to the appropriate PNA oligomer. This effect of PCR clamping was exploited in the following two ways: (i) analysis of gene libraries generated by PCR clamping with PNA-ALF together with standard libraries reduced the number of clones which had to be analyzed to detect all of the different sequences present in an artificial rDNA mixture; and (ii) PCR clamping with PNA-EUB353 and PNA-1114F was used to selectively recover rDNA sequences which represented recently described phylogenetic groups (NKB19, TM6, cluster related to green nonsulfur bacteria) from an anaerobic, dechlorinating consortium described previously. We concluded that PCR clamping might be a useful supplement to standard PCR amplification in rDNA-based studies of microbial diversity and could be used to selectively recover members of undescribed phylogenetic clusters from complex microbial communities.